Increased bone morphogenetic protein 7 signalling in the kidneys of dogs affected with a congenital portosystemic shunt. Issue 2 (May 2015) - van Dongen, Astrid M.; Heuving, Susanne M.; Tryfonidou, Marianna A.; van Steenbeek, Frank G.; Rothuizen, Jan; Penning, Louis C.
Highlights: Often dogs with a congenital portosystemic shunt present with enlarged kidneys. Bone morphogenetic protein 7 signalling was compared in kidneys. Renal BMP-7 signalling was increased in dogs affected with a CPPS. Abstract: Dogs with a congenital portosystemic shunt (CPSS) often have enlarged and hyper-filtrating kidneys. Although expression of different growth factors has been well-described in the livers of dogs affected with a CPSS, their expression in the kidneys has yet to be determined. Bone morphogenetic protein 7 (BMP-7), hepatocyte growth factor (HGF) and transforming growth factor (TGF)-β have been implicated in renal development (BMP-7, HGF) or the onset of renal fibrosis (TGF-β). Moreover, BMP-7 and HGF have protective properties in renal fibrosis. In this study, the expression and activity of BMP-7 were investigated in renal biopsies obtained from 13 dogs affected with a CPSS and compared to similar samples from age-matched healthy control dogs. Both quantitative reverse-transcriptase PCR and Western blotting showed up-regulated BMP-7 signalling in kidneys of CPPS-affected dogs. These research findings may help to explain the renal pathology/dysfunction in dogs affected with a CPSS.